(untitled) (Journal of science and technology exploration, 2026)
With the iterative upgrading of technologies such as digital graphics, artificial intelligence, real-time rendering, and virtual simulation, three-dimensional animation creation has completely moved beyond the limitations of traditional manual production and has formed a standardized, intelligent, and efficient full-process creation system. Digital technology has deeply penetrated all stages of three-dimensional animation, including pre-production planning, mid-production, and post-production compositing. It has not only reconstructed the animation production workflow, but also promoted the innovation of visual presentation from realistic simulation toward diversified, immersive, and artistic expression. From the perspective of the full process of three-dimensional animation creation, this paper systematically explores the application value of digital technology in concept design, model construction, animation rigging, special effects rendering, and post-production optimization. It analyzes the innovative characteristics and existing problems of current three-dimensional animation visual presentation, and proposes optimization paths in light of industry development trends, so as to provide theoretical reference and practical guidance for high-quality three-dimensional animation creation and visual innovation in the new era.